The Influence Of Work Discipline And Work Motivation On Employee Performance In The Police Civil Servants (Satpol-Pp) Of Empat Lawang Regency - Donny Febrian; M. Pahlan; Kasinem Kasinem (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the influence of work discipline and work motivation on employee performance in the Civil Service Police Unit (Satpol-PP). The results showed that (1) work discipline has a significant partial effect on performance, as evidenced by the calculated t value > t table (4.370 > 2.042). (2) work motivation has a significant partial effect on performance, as evidenced by the calculated t value > t table (3.558 > 2.042). (3) work discipline and work motivation have a significant simultaneous effect on performance, as evidenced by the calculated f value > f table (24.531 > 4.171), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).